2009
DOI: 10.1136/emj.2008.059733
|View full text |Cite
|
Sign up to set email alerts
|

Is ambulance telephone triage using advanced medical priority dispatch protocols able to identify patients with acute stroke correctly?

Abstract: Fewer than half of all patients with acute stroke were identified using telephone triage on the initial emergency call to the ambulance service. Less than one quarter received the highest priority of ambulance response. This first link in the chain of survival needs strengthening in order to provide prompt and timely emergency care for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
2
41
2
1
Order By: Relevance
“…[7][8][9] If this is to be increased, it is necessary to identify those symptoms likely to have a high sensitivity in relation to a final diagnosis of stroke. The characteristics with the highest sensitivities were having no to only slight pre-stroke disability, and being alert.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] If this is to be increased, it is necessary to identify those symptoms likely to have a high sensitivity in relation to a final diagnosis of stroke. The characteristics with the highest sensitivities were having no to only slight pre-stroke disability, and being alert.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, delays in presentation and specialist assessment frequently prevent patients from receiving rtPA. Emergency medical dispatch sensitivity and positive predictive value (PPV) for identifying stroke is < 50%, [7][8][9] and this is compounded by long delays in patients accessing emergency medical services (EMSs). 10 Studies have shown that activation of the EMSs is the single most important factor in the rapid triage and treatment of acute stroke patients.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that the CDSS is often oversensitive (it does not miss sick patients and therefore it is safe) but that it tends to 'over-triage' (it identifies 'too many' false positives because it is not specific enough). 47,48 Such studies acknowledge that it is difficult to devise a CDSS that has both high sensitivity and high specificity, and in a CDSS that has been designed for use by non-clinicians it is necessary -and somewhat inevitable -that NHS Pathways has high DISCUSSION AND CONCLUSIONS sensitivity. It is possible that NHS Pathways 13,15 may 'over-triage', particularly to ambulance services; however, more work is required to clearly understand this.…”
Section: Implications For Nhs 111 As a Standardised Servicementioning
confidence: 99%
“…Emergency medical services (EMS) is the first medical contact for half of the acute stroke patients. Thus, they play an undeniable role in survival and prevention of complications in these patients [4]. Getting "the right patient to the right place in time" is the key to save lives and reduce disability caused by stroke [5].…”
Section: Introductionmentioning
confidence: 99%